Active Ethical Leadership, Giftedness, and Creativity. Issue 4 (2nd October 2017) - Runco, Mark A.
Abstract : This commentary is focused on Robert Sternberg's new Active Concerned Citizenship and Ethical Leadership (ACCEL) model. The new model is well conceived and goes far beyond existing models. It is especially attractive in that the emphasis is on ethics. Now more than ever before there is a clear need for education to support ethical reasoning and behavior, and if this is coupled with active and concerned citizenship, as Sternberg proposes, we may find talents that are as of yet untapped and enormously useful for society.